O processo de decisão política e a Zona Franca de Manaus - Mendonça, Mauricio Brilhante (2013)
The Manaus Free Trade Zone (ZFM) is the Union’s regional development policy for the Western Amazonia which is based on the concession of tax incentives to the productive capital. Its main results can be seen in the Industrial Pole of Manaus (PIM). Based on theoretic references on public policies, political decision process and on the framework of historical institutionalism, the thesis analyses three relevant decisions to the ZFM, as well as the public agencies where these decisions are made, characterizing the actors who influence them while also trying to understand the flow of public decisions in each one of the decision making processes. The first one of them refers to the two moments in which the decision of extending the ZFM’s applicability was being discussed in the National Congress, when interest groups were capable of joining their political forces to guarantee the constitutional status of the ZFM. The second one refers to the evaluation of the implantation, update, diversification or extension’s pleas of the industrial projects in the ZFM, on which the research provided understanding that once the technical-economical project is coherently presented, according to the established Basic Productive Process (PPB), the legislation and accompanied by the necessary documentation, the projects of whichever sector will not face any difficulty to be approved by the CAS. The need of a previous PPBs existence makes their establishment process a vital decision in the ZFM policies. This is the third process. PPB is the tool which has allowed the ZFM’s tax incentives’ policy’s governance through the regularization of processes and procedures which are to be abode by the companies which enjoy the benefits. The PPBs are established after negotiation among producers, suppliers and the Federal State, this last one being represented by MDIC, MCTI and SUFRAMA, under the GT-PPB’s management, whose operation is regulated by means of the Interministerial Ordinance MDIC/MCT n°170/2010. The PPB has been used by the State to establish counterparts to the companies which benefit from the ZFM’s tax incentives and also to allow the installation of productive sectors in that zone. It was noted that what is effectively valued is the risk of the PPB being published causing, therewith, the displacement of other productive plants from different regions in Brazil to the ZFM, situation which would turn into a negative decision. However, in cases in which the other federation units, cities or micro regions’ loss is not clear, there may be conflicts of political character, which leaves the decision to be made by negotiation levels and power above the GT-PPB. It is important to mention that the GT-PPB members understand that the ZFM is a public policy for the Western Amazonia, and also that they recognize the power that these members’ functions altogether have, each one with their own specialty, limits and objectives, functions which may influence the formulation and implementation of the industrial, science and technology and regional development policy in Brazil. It was possible to notice the participants’ effort with the current rules to promote improvements in these policies as well as the fact of how these teams are reflected by the lack of an effective national productive development project.